GENDER EQUALITY AND SUSTAINABLE DEVELOPMENT: THE ROLE OF WOMEN WELFARE PROGRAMMES IN SOCIAL TRANSFORMATION - Gandhi, Anika; Das, Lopamudra (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Gender equality and women's empowerment are universally recognised as foundational prerequisites for sustainable development, enshrined in the United Nations Sustainable Development Goal 5 (SDG 5) of the 2030 Agenda. Despite substantive policy commitments and the proliferation of women welfare programmes across India, the translation of these interventions into lasting social transformation remains uneven, contested, and insufficiently evidenced at the aggregate level. This study undertakes a systematic secondary data analysis to examine the role of women welfare programmes in advancing gender equality and fostering sustainable social transformation in India. Drawing upon nationally representative and internationally validated datasets — including the National Family Health Survey-5 (NFHS-5, 2019-21), NFHS-4 (2015-16), the Periodic Labour Force Survey (PLFS, 2022-23), the World Economic Forum Global Gender Gap Report (2023), the UNDP Gender Inequality Index (2022), the Economic Survey 2022-23, and MoWCD Annual Reports — the study evaluates trends across economic empowerment, educational attainment, health and nutrition, and social and political agency dimensions. Findings reveal that welfare programmes have produced measurable gains across key access indicators: women's bank account ownership rose by 25.6 percentage points to 78.6%; institutional delivery rates reached 88.6%; and the SHG ecosystem now covers 142 million families through 12 million women-led groups. However, structural transformation indicators — spousal violence (−1.8 pp), child marriage (23.3%), and cash-paid employment (+0.8 pp) — remain near-stagnant, exposing a fundamental paradox at the heart of India's gender policy: impressive programme reach has not yet produced commensurate changes in power relations, economic agency, or social norms. The study contributes an intersectional, multi-source analytical framework to the gender equality literature and concludes with evidence-based policy recommendations for rights-based, convergent, and intersectional welfare programme design.